Are Teachers Agents of Change? Teacher Training and The Gender Dimension in Adult Education: Italy and Nigeria in Comparison - Valentina Guerrini; Denise Tonelli; Bolanle C. Simeon-Fayomi (Firenze University Press, 2020)
Adult education can play a fundamental role in changing existing gender hierarchies, breaking down gender stereotypes, and promoting gender equality. Teachers can be important agents of change, but they not only have to be aware of their behaviours, attitudes, and views, they also have to be able to understand the specific needs and interests of learners, to use gender-based methods, and to implement practices free of gender stereotypes. In order to do this, adequate education and training are needed, but both in Italy and Nigeria, gender issues are not part of the education and training curriculum, and much remains to be done for raising awareness of this issue.
Keywords: Teacher training; gender equality; women's empowerment; adult education; lifelong learning